2000
DOI: 10.1007/s00223001125
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Interleukin-6 Release in Human Osteoblast-Like Cells Exposed to Titanium Particles In Vitro

Abstract: Orthopaedic wear debris induces release of bone-resorbing factors from macrophages and fibroblasts. However, the extent to which elemental metallic particles induce bone cells to express factors contributing to implant loosening remains unclear. This study showed that exposure of MG-63 osteoblast-like cells to titanium particles at a concentration of 0.30% v/v resulted in a 15-fold increase in IL-6 release into the culture medium after 24 hours, when compared with cells without particles. Northern blots reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
29
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 25 publications
9
29
0
Order By: Relevance
“…Previous studies have shown that hOB are capable of IL-6 production in response to proinflammatory cytokines such as IL-1 and TNF and in response to solid particles such as wear debris of various types (18,20,21). Inflammatory microcrystals also stimulated the generation of IL-6 by hOB as reported here.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous studies have shown that hOB are capable of IL-6 production in response to proinflammatory cytokines such as IL-1 and TNF and in response to solid particles such as wear debris of various types (18,20,21). Inflammatory microcrystals also stimulated the generation of IL-6 by hOB as reported here.…”
Section: Discussionsupporting
confidence: 81%
“…The present data indicate that the activation of hOB by MSUM and CPPD microcrystals did not require their internalization by the target cells. Moreover, the functional response of hOB to MSUM and CPPD microcrystals in term of stimulation of PGE 2 and IL-6 production or in term of inhibition of 1,25(OH) 2 D 3 -induced alkaline phosphatase and osteocalcin was of a similar magnitude to that previously reported with various prosthetic wear particles (17,18 (40), the most abundant eicosanoid in bone with anabolic or catabolic effects depending on its local concentration. The present study indicated that MSUM or CPPD microcrystals were capable of stimulating hOB to express a significant activity of COX-2 at concentrations lower than those previously reported for activation of neutrophils in vitro (28,(41)(42)(43)(44)(45).…”
Section: Discussionsupporting
confidence: 79%
“…However, the exact effect of titanium on cells is still not well characterized [1]. One of the few studies showed that osteoblast-like cells respond to titanium particles through increased expression of the proinflammatory cytokine interleukin-6 in a process requiring phagocytosis and intracellular signalling pathways [3]. It has also been reported that approximately one third of patients with titanium alloy spinal implants exhibited abnormal 0162-0134/$ -see front matter 脫 2004 Elsevier Inc. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…4 Previous in vitro studies have reported that Ti particles can elicit bone resorption primarily by inducing osteoclast differentiation 5 and this process may be partly mediated by stimulated cytokine release and increased expression of receptor activator of nuclear factor 魏B ligand (RANKL) by osteoblastic cells. [6][7][8] Tissue responses to Ti particles in vivo have also been reported. Agins et al 9 and Witt and Swann 10 reported that metallosis due to Ti particles was associated with the invasion of numerous histiocytes containing metallic debris into the synovial membrane and periarticular soft tissues.…”
Section: Discussionmentioning
confidence: 96%